In vitro antidiabetic effects of flavonoids: molecular and structure-activity relationship based study - Sarian, Murni Nazira; Ahmed, Qamar Uddin; Alhassan, Alhassan Muhammad; Bakhtiar, M. Taher; Arief Ichwan, Solachuddin Jauhari; Latip, Jalifah (2018)
Several in vitro and in vivo studies have shown antidiabetic potential of flavonoids. These polyphenolic compounds biochemical properties are in fact structure dependent, however, yet to be clearly understood. Hence, the chief objective of this study was to determine the antidiabetic activities of some structurally related flavonoids to recognize important positions responsible, their correlation, as well as the effect of derivatisation on the same properties. 15 selected flavonoids were subjected to cytotoxicity test (MTT) on two different cell lines namely RIN-5F pancreatic and 3T3-L1 pre-adipocytes. Subsequently, the compounds were subjected to in vitro antidiabetic investigation using RIN-5F to determine the insulin secretagogue activity via ELISA as well as on 3T3-L1 adipocytes to determine the insulin sensitizing activity via adipogenesis and fluorescence glucose uptake tests. Next, the adipokines viz. leptin, tumor necrosis factor-α (TNF-α), adiponectin, and retinol binding protein-4 (RBP-4) were measured to investigate the biochemical reactions. Afterward, western blotting was performed to check GLUT4, PPARγ and PPARα protein expressions. To further understand the mechanism, molecular docking study was executed against same proteins. The structures of all flavonoids were elucidated through 1H-and 13C-NMR spectroscopy. Results showed that the total number and the configuration of hydroxyl groups, presence of C-2-C-3 double bond as well as C-4 ketonic group play important roles in regulating antidiabetic activity which help to enhance the glucose uptake via PPAR and GLUT4 protein receptors. The results might prove worthy of developing semi-synthetic analogs that may retain substantial antidiabetic capacity.